2017
DOI: 10.1136/annrheumdis-2017-211472
|View full text |Cite
|
Sign up to set email alerts
|

Weight loss for overweight and obese individuals with gout: a systematic review of longitudinal studies

Abstract: ObjectivesWeight loss is commonly recommended for gout, but the magnitude of the effect has not been evaluated in a systematic review. The aim of this systematic review was to determine benefits and harms associated with weight loss in overweight and obese patients with gout.MethodsWe searched six databases for longitudinal studies, reporting the effect of weight loss in overweight/obese gout patients. Risk of bias was assessed using the tool Risk of Bias in Non-Randomised Studies of Interventions. The quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
89
0
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(96 citation statements)
references
References 62 publications
0
89
0
7
Order By: Relevance
“…Thus, these results do not indicate that lixisenatide affects UE UA . Finally, UA levels were unaffected by either GLP‐1RA in our prolonged intervention studies, despite decreases in body weight, thus potentially improving insulin resistance …”
Section: Discussionmentioning
confidence: 79%
“…Thus, these results do not indicate that lixisenatide affects UE UA . Finally, UA levels were unaffected by either GLP‐1RA in our prolonged intervention studies, despite decreases in body weight, thus potentially improving insulin resistance …”
Section: Discussionmentioning
confidence: 79%
“…Obesity increases gout risk by raising the serum urate level, through both decreased renal urate excretion and increased urate production (48)(49)(50)(51)(52)(53). Mendelian randomization studies have shown obesity to be causally associated with serum urate levels in the general population (54,55), and weight loss through bariatric surgery or lifestyle intervention leads to reductions in serum urate levels (56). Prompted by an interest in examining the strong biologic mechanism and plausibility of intake of purine, fructose, and alcohol, previous metabolic loading experiments examining these factors (57)(58)(59)(60)(61)(62)(63)(64)(65) have confirmed their serum urate-raising effects, whereas dairy products were shown to have uratelowering effects in 3 experimental studies, including 2 randomized trials (66)(67)(68).…”
Section: Discussionmentioning
confidence: 99%
“…Also, unfavorable effects may occur in the short term. 230 Therefore, HU therapy requires comprehensive concerns far beyond only obesity management. The first concern encompasses lifestyle management, such as diet.…”
Section: The Therapeutic Strategy Of Hyperuricemiamentioning
confidence: 99%